Exposure to Violence in High School Students in Ciudad Juarez, Mexico - Saucedo, Irene Concepción Carrillo; Alvarado, Priscila Montañez; Del Villar, Oscar Armando Esparza; Vega, Marisela Gutiérrez; Peña, Gloria Margarita Gurrola (European Scientific Journal, ESJ, 2017)
The purpose of the present study was to survey high school students, and explore the relationship between the scales of Behavioral Resilience, Paranoid Thoughts, Posttraumatic Stress Disorder, Patient Health Questionnaire Depression PHQ-9 and the Multidimensional of Fatalism. The sample was composed of 300 high school students with a mean age of 16.75 years (SD=0.69), with an age range of 15 to 19 years, where 64.2% reported being female. According to the results, significant correlations were found in most of the scales applied, except for the fatalism scale.